Matrix Tablets Based on Chitosan-Carrageenan Polyelectrolyte Complex: Unique Matrices for Drug Targeting in the Intestine - Komersová, Alena; Svoboda, Roman; Skalická, Barbora; Bartoš, Martin; Šnejdrová, Eva; Mužíková, Jitka; Matzick, Kevin (Pharmaceuticals (Basel, Switzerland), 2022)
The present study focused on the more detailed characterization of chitosan-carrageenan-based matrix tablets with respect to their potential utilization for drug targeting in the intestine. The study systematically dealt with the particular stages of the dissolution process, as well as with different views of the physico-chemical processes involved in these stages. The initial swelling of the tablets in the acidic medium based on the combined microscopy-calorimetry point of view, the pH-induced differences in the erosion and swelling of the tested tablets, and the morphological characterization of the tablets are discussed. The dissolution kinetics correlated with the rheological properties and mucoadhesive behavior of the tablets are also reported, and, correspondingly, the formulations with suitable properties were identified. It was confirmed that the formation of the chitosan-carrageenan polyelectrolyte complex may be an elegant and beneficial alternative solution for the drug targeting to the intestine by the matrix tablet.
Keywords: polyelectrolyte complex; chitosan; carrageenan; drug targeting